Performing Manhood: Glahn and the Masculinity Crisis in Hamsun’s ‘Pan’ - He, Chengzhou (Nordlit, 2016)
In Hamsun’s novel Pan, Lieutenant Glahn holds an essentialist notion of masculinity that is somewhat outdated in the context of emerging Norwegian modernity. His acts of violence, which are performative of his male pride, not only bring harm to others, but also become destructive to himself. The masculinity crisis enacted in Pan is put into the context of the social, historical, and cultural changes related to gender and modernity that occurred during the end of the 19th century in Norway and beyond.